An action research on enhancing the handling process of existing time deposits in Bonifacio Global City (BGC) priority under Local Banking Corporation - Villapando, Joyce Marian T. (Animo Repository, 2020)
This action research primarily focused on enhancing the handling process of existing Time Deposits of Local Banking Corporation- BGC Priority Center which addressed the issue on the failure to meet the deadline set by Local Banking Corporation- BGC branch in relation to sending instructions for existing Time Deposit maturities. This was due to absence of clear process in handling maturities, non-compliance of Local Banking Corporation- BGC Priority Center in sending Time Deposit Maturities to Local Banking Corporation- BGC branch on or before 2:00 pm, and no standardized email template on sending Time Deposit instructions. Initial observations on the abovementioned issue include delayed submission of instructions from Relationship Managers (RMs), continuous follow-ups from New Accounts Clerk (NAC), and frequent requests from customers of Local Banking Corporation- BGC Priority Center to extend the sending of instructions to RMs. The objectives of this action research are the following: 1) to improve customer service, 2) to tighten the handling process of Time Deposit maturities, 3) to improve communication among the team, and 4) to reduce customer complaints/ requests. First, second, and third person inquiry tools were utilized to support this action research. Other than personal observations, data was gathered from various collaborations, including oneon-one interviews, group meetings, and focused group discussions. On the other hand, DMAIC Methodology was applied as theoretical base of the actions. Two (2) cycles were implemented throughout the whole action research. First cycle was the centralization of Time Deposit instructions to the Customer Relations Officer (CRO) while the second cycle was the standardization of email template for sending Time Deposit instructions to the NAC. Though the team was able to meet 2 out of 4 of its objectives, second cycle was conducted to achieve improvement in communication between BGC branch and BGC Priority Center. Lastly, a new framework was formed which could be used for future research.